Korean clinical practice guidelines for preventing the transmission of infections in hemodialysis facilities - Hayne Cho Park; Young-Ki Lee; Kyung Don Yoo; Hee Jung Jeon; Seung Jun Kim; Ajin Cho; Jacob Lee; Yang-Gyun Kim; Sang-Ho Lee; Sang-Oh Lee (The Korean Society of Nephrology, 2018)
Patients receiving hemodialysis are vulnerable to infectious diseases due to their impaired immunity and high risk of exposure to pathogens. To protect patients, staff, and visitors from potential infections, each hemodialysis unit should establish and follow standard infection control and prevention measures. Therefore, clinical practice guidelines were developed by a working group of nephrologists and infection control specialists to provide evidence-based guidance for dialysis physicians and nurses, with the aim of preventing infection transmission and controlling infection sources in hemodialysis facilities. The areas of infection control covered by these guidelines include standard precautions, isolation strategies, vascular access, water treatment, cleaning/disinfecting/sterilizing, and vaccination. This special report summarizes the key recommendations from the Korean clinical practice guidelines for preventing the transmission of infections in hemodialysis facilities.